2022
DOI: 10.1108/tlo-01-2022-0015
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable human resources management in learning organizations: consequences of customer incivility and surface acting

Abstract: Purpose Because of the nature of their work, frontline service employees are highly exposed to customer incivility (CI) and are required to perform surface acting (SA) in such circumstances. Both CI and SA have detrimental impact to a sustainable workforce. This study aims to investigate the psychological effects of CI and SA on emotional exhaustion (EE), organizational commitment (OC) and work–family conflict (WFC). Design/methodology/approach Data from 203 respondents who successfully completed the questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 110 publications
1
12
0
Order By: Relevance
“…It can be defined as “low-intensity deviant behavior with ambiguous intent to harm the target, in violation of workplace norms and mutual respect” (Andersson and Pearson, 1999, p. 457). Discourteous behavior can include the active or passive expression of disrespect, such as ignoring or interrupting a colleague and publicly issuing a reprimand (Kuok et al , 2022). Such behavior may be inconspicuous for a time but has the potential to escalate into more aggressive behavior in the workplace (Kim & Qu, 2019).…”
Section: Can Customers Pose a Threat To A Sustainable Workforce?mentioning
confidence: 99%
See 2 more Smart Citations
“…It can be defined as “low-intensity deviant behavior with ambiguous intent to harm the target, in violation of workplace norms and mutual respect” (Andersson and Pearson, 1999, p. 457). Discourteous behavior can include the active or passive expression of disrespect, such as ignoring or interrupting a colleague and publicly issuing a reprimand (Kuok et al , 2022). Such behavior may be inconspicuous for a time but has the potential to escalate into more aggressive behavior in the workplace (Kim & Qu, 2019).…”
Section: Can Customers Pose a Threat To A Sustainable Workforce?mentioning
confidence: 99%
“…Employees may also suffer from emotional exhaustion and burnout for other reasons, such as interactions with external stakeholders, especially customers. In this issue, Kuok et al (2022) address the problem of customer inclivity and the resulting surface acting behavior of employees. Workplace inclivity has been known to cause a toxic work environment in the workplace.…”
Section: Sustainable Workforce In Teleworkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizations consider surface acting important because they expect that it increases their business and profit (Yanchus et al ., 2010). However, evidence has shown that surface acting harms both individuals and organizations by increasing job burnout and deviant behavior (Kuok et al. , 2022) and these harmful effects are not limited to the workplace but spill over into employees' family lives, where they spur conflict (Gu et al ., 2020; Zhu et al ., 2021).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…In a study of the frontline workers' performance in public sector (Kuok, Chan, Kou, Kong, & Mac, 2022), the psychological effects of customer incivility and surface acting and related impacts on building a learning organization are examined. The survey results indicate that customer incivility increases emotional exhaustion and induces work withdrawals, which undermine the learning potential of publication organizations.…”
Section: Overview Of Contributions In This Special Issuementioning
confidence: 99%